2020
DOI: 10.3390/biom10071021
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis-Inducing Factor, Mitochondrion-Associated 3 (AIFM3) Protein Level in the Sera as a Prognostic Marker of Cholangiocarcinoma Patients

Abstract: Prognosis of cholangiocarcinoma (CCA) patients is absolutely poor. Since improvement of prognosis and/or response to treatment by personalized and precision treatments requires earlier and precise diagnostic markers, discovery of prognostic markers attracts more attention. Apoptosis-inducing factor, mitochondrion-associated 3 (AIFM3) is highly expressed in several cancers including CCA. The present study investigated whether the serum AIFM3 level can be used as a potential marker for CCA prognosis. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…For instance, HSP60 is primarily localized in the eukaryotic mitochondria and its overexpression in the sera is used as a biomarker for the diagnosis and prognosis of several cancers, including colorectal and breast cancers [29,30]. Recently, two mitochondrial proteins-PDK3 and AIFM3-in the sera have been determined and can be used as a prognostic marker for CCA [11,12]. The present results showed that CIAPIN1 is also a mitochondrial protein marker in the sera of CCA patients.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…For instance, HSP60 is primarily localized in the eukaryotic mitochondria and its overexpression in the sera is used as a biomarker for the diagnosis and prognosis of several cancers, including colorectal and breast cancers [29,30]. Recently, two mitochondrial proteins-PDK3 and AIFM3-in the sera have been determined and can be used as a prognostic marker for CCA [11,12]. The present results showed that CIAPIN1 is also a mitochondrial protein marker in the sera of CCA patients.…”
Section: Discussionsupporting
confidence: 54%
“…The Venn diagram indicated six CCA-related mitochondrial proteins, including nuclear receptor coactivator 1 isoform 3 (NCOA1), apoptosis-inducing factor, mitochondrion-associated 3 (AIFM3), transitional endoplasmic reticulum ATPase (VCP), CIAPIN1, PRKCA-binding protein (PICK1), and peptidyl-prolyl cis-trans isomerase D (PPID). Among those, AIFM3 was excluded due to it already being detected in the sera of CCA and HC [12]. Tools in the Gene Expression Profiling Interactive Analysis 2 (GEPIA2) databases were used to evaluate the expression levels of the genes of these five proteins unique in CCA (Figure 1b-f).…”
Section: Bioinformatic Analysis Of Mitochondrial Protein Database And...mentioning
confidence: 99%
“…The results shown above suggested potential roles of AIFM3 in migration and invasion of CCA cells. In our previous study, higher serum AIFM3 levels were significantly associated with lymph node metastasis and shorter overall survival of CCA patients (13). Here, we examined the expression of AIFM3 in CCA tissues with or without lymph node metastasis.…”
Section: (A) the Probability Of Binding Between Apoptosisinducing Fac...mentioning
confidence: 86%
“…AIFM3 is highly expressed in breast cancer tissues and is significantly associated with the clinical outcome of breast cancer patients (25). Our recent study revealed that higher serum AIFM3 levels are associated with lymph node metastasis and shorter overall survival of patients with CCA (13). In this study, we intended to elucidate the biological roles of AIFM3 and the related signaling pathways in CCA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation